Business and Human Rights (GESTIÓN Y TENDENCIAS, 2017)
Economic activity, both public and private, usually has a direct impact on the people and communities operating both around it and within it. The consequences for the environment and for health, the impairment of the rights of communities —especially indigenous communities— and the violation of workers' fundamental rights, particularly through discriminatory measures of various kinds, are the most recurrent examples of an increasingly pressing reality. This article sets out the challenge for companies of reviewing their forms of organization in order to properly discharge these responsibilities.